Computer science and engineering - Weber, G.-W. (Elsevier B.V., 2018)
During previous decades, modern approaches to Operational Research (OR), Computation and Optimization have attracted a growing number of scientists, pedagogues, advisors, deciders and practitioners. Actually, very strong and smart (âintelligentâ) computational techniques arose for handling a very large number of real-world challenges and crises, in particular, in relation with the main areas of optimization in theory and practical use. Those real problems are characterized by their tremendous non-convexity and complexity. In the communities of OR, Analytics and Computation worldwide, researchers and investigators from different fields, spectra, continents and regions have cooperated to find smart answers for those striking and urgent difficulties. Within that scientific global family, there are scholars from IFORS, its regional groupings and, inside of them, national OR societies and working groups. High increase of human population, feeling of being lonely or lost, problems with the fast process of âglobalizationâ, related âlossesâ everywhere on the globe, illness, societal conflicts and wars, prove that the âHuman Factorâ ought to be considered and taken into account much more than in past eras by researchers, educators, leaders, engineers, officials, and also medical doctors, advisers and trainers. Important representations and incorporations of the âHuman Factorâ through Intelligence, Humanity and Humility should be hosted to a rising degree in the areas of OR, Analytics and Computation. Â© 2018